Dobutamine stress testing for the evaluation of atrial and diastolic ventricular function in Fontan patients - Willem A Helbing; Livia Kapusta; Irene M Kuipers; Arend D J Ten Harkel; Lucia J M Kroft; Jelle P G van der Ven; Sjoerd S M Bossers; Eva van den Bosch; Niels Dam; Gabrielle G van Iperen (Open Heart)
Objective To assess the atrial and ventricular diastolic function response to dobutamine stress in Fontan patients, and to relate these measurements to exercise capacity and events during the follow-up.Methods We performed a secondary analysis of a cross-sectional multicentre study of Fontan patients with intra-atrial lateral tunnel (ILT) or extracardiac conduit (ECC) modification. Subjects underwent cardiac MRI during rest and low-dose dobutamine stress, and cardiopulmonary exercise testing. Atrial and diastolic ventricular function parameters were derived from volume-time curves.Medical records were abstracted for a composite end-point of death, listing for transplant, arrhythmia and reintervention. Spearman’s r correlation tests and Cox proportional hazards models were used to assess the relation between the dobutamine response for atrial and diastolic ventricular function and outcomes, including exercise capacity.Results We included 57 patients (26 ECC; 31 ILT) aged 12.8 (IQR (10.3–15.5)) years. During dobutamine stress atrial cyclic volume change increased (3.0 (0.4–5.9) mL/m2, p<0.001), as did early (1.9 (−1.6 to 3.6) mL/m2, p=0.001) and late emptying volume (2.2 (0.2–4.4) mL/m2, p<0.001).Ventricular early filling decreased (−1.6 (−5.7 to 0.7) mL/m2,p=0.046) and ventricular late filling increased (1.0 (−0.4 to 3.4) mL/m2,p<0.001) while stroke volume remained similar.Only for patients with the ECC modification, atrial early emptying volume increase correlated with peak oxygen uptake (ρ=0.66,p=0.002). No other parameter related to exercise capacity.During a median 7.1-year follow-up, 22 patients reached the composite endpoint. No parameter predicted events during the follow-up.Conclusions Dobutamine stress augmented atrial reservoir and pump function for Fontan patients. Atrial early emptying reserve related to exercise capacity in ECC patients. No other atrial or diastolic ventricular function parameter related to outcomes.